An insulating doped antiferromagnet with low magnetic symmetry as a room temperature spin conduit - Ross, Andrew; Lebrun, Romain; Baldrati, Lorenzo; Kamra, Akashdeep; Gomonay, Olena; Ding, Shilei; Schreiber, Felix; Backes, Dirk; Maccherozzi, Francesco; Grave, Daniel A; Rothschild, Avner; Sinova, Jairo; et al. (arXiv.org, 2020)
We report room temperature long-distance spin transport of magnons in antiferromagnetic thin film hematite doped with Zn. The additional dopants significantly alter the magnetic anisotropies, resulting in a complex equilibrium spin structure that is capable of efficiently transporting spin angular momentum at room temperature without the need for a well-defined, pure easy-axis or easy-plane anisotropy. We find intrinsic magnon spin-diffusion lengths of up to 1.5 μm, and magnetic domain governed decay lengths of 175 nm for the low frequency magnons, through electrical transport measurements demonstrating that the introduction of non-magnetic dopants does not strongly reduce the transport length scale showing that the magnetic damping of hematite is not significantly increased. We observe a complex field dependence of the non-local signal independent of the magnetic state visible in the local magnetoresistance and direct magnetic imaging of the antiferromagnetic domain structure. We explain our results in terms of a varying and applied-field-dependent ellipticity of the magnon modes reaching the detector electrode allowing us to tune the spin transport.